Analisis Strategi Pemasaran pada UMKM di Sektor Makanan dan Minuman di Jalan Rajawali Kota Palangka Raya - Lega Risma Alfioni; Tonich Uda; Fendy Hariatama H (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the marketing strategies implemented by Micro, Small, and Medium Enterprises (MSMEs) in the food and beverage sector in Palangkaraya City to enhance competitiveness and sales performance. The research is motivated by the rapid growth of MSMEs in Indonesia, particularly in the culinary sector, which significantly contributes to the national economy but faces intense market competition. The research method employed is with data collected through interviews, observations, and documentation of MSME owners. The findings reveal that most entrepreneurs have utilized digital media such as Instagram, Tiktok, and food delivery platforms for promotion, yet many have not conducted systematic market analysis. Key factors such as the choice of promotional channels, pricing strategies, product packaging, and understanding of local consumer trends significantly affect the effectiveness of marketing strategies. This study recommends the importance of structured marketing planning, optimal use of social media, and enhanced digital literacy to enable MSMEs to compete and grow sustainably.